HIPK4 accelerates cutaneous squamous cell carcinoma progression by phosphorylating TAp63 and inhibiting EFEMP1 expression - Guo, Ze; Chen, Bingjie; Zhang, Mengya; Gao, Min; Wang, Zaixing; Tang, Huayang; Tang, Xianfa; Zhang, Qian; Utikal, Jochen (The journal of biological chemistry, 2025)
Cutaneous squamous cell carcinoma (CSCC) is a common skin cancer with a tendency to metastasize, leading to poor patient prognosis. Homeodomain interacting protein kinase 4 (HIPK4) has been identified as a key inhibitor of human skin epithelial differentiation. However, the role of HIPK4 in regulating CSCC development remains unclear. Our preliminary experiment showed that HIPK4 was highly expressed in CSCC tumor tissues and cells. In this study, we investigate the role of HIPK4 in regulating CSCC progression and the underlying mechanisms. In the current study, the interaction between HIPK4 and TAp63 was analyzed by Co-IP and GST-pull down assays, and the relationship between TAp63 and EFEMP1 was analyzed by ChIP and dual luciferase reporter assays. Our results showed that EFEMP1 expression was decreased in CSCC tissues and cells, and EFEMP1 overexpression inhibited CSCC cell proliferation, migration, and invasion. In addition, HIPK4 was upregulated in CSCC; knocking down HIPK4 suppressed CSCC cell malignant behaviors and tumor growth in mice. Mechanistically, HIPK4 promoted tumor progression by phosphorylating the tumor suppressor TAp63 at Ser395, leading to decreased expression of EFEMP1, a key extracellular matrix protein with anti-tumor properties. As expected, the inhibitory effects of HIPK4 knockdown on CSCC cell malignant behaviors were reversed by EFEMP1 knockdown. In summary, HIPK4 could exacerbate CSCC malignant progression by inhibiting EFEMP1 through phosphorylating TAp63, highlighting HIPK4 as a potential therapeutic target in CSCC. Our results provide new insights into the molecular mechanisms underlying CSCC progression and propose novel strategies for therapeutic intervention.